Enhancing College Access in Zimbabwe: Impact of Student Loans and Grants - Muchimba, Lackson; Dwi Liestiawati, Fibria Indriati (Policy & Governance Review, 2024)
This study explores how government interventions, grants, and loans influence college access in Zimbabwe, focusing on understanding the factors affecting college access and retention rates. The research aims to inform evidence-based decision-making regarding college access through a mixed research approach integrating qualitative and quantitative methods. Combining both qualitative and quantitative methods to ensure the validity and reliability of the findings. It analyses secondary data sources, such as literature, reports, and statistical datasets, to explore aspects like college access, enrollment trends, poverty rates, financial aid programs, and student loan systems in Zimbabwe. Triangulation techniques enhance the credibility of the study's findings by integrating evidence from various sources and employing diverse data collection and analysis methods, enriching perspectives and strengthening the validity and reliability of the study's conclusions. Key findings suggest that grants and loans significantly contribute to increasing college enrollment rates, particularly among economically disadvantaged groups. However, enrollment disparities persist, especially among marginalized populations like women. Despite a modest increase in government spending on education, concerns arise due to a slowdown in overall enrollment growth. Barriers to student loan uptake include complex application processes, concerns about debt burdens, and uncertainties regarding post-graduation employment prospects. The study emphasizes the importance of comprehensive policy interventions to simplify eligibility criteria, enhance financial literacy, and promote employment pathways. Using human capital and open systems theories, the research lays a groundwork for evidence-based decision-making to enhance access to higher education in Zimbabwe.